Slow Relaxation of the Magnetisation in a Two-Dimensional Metal–Organic Framework with a Layered Square Lattice - Samia Benmansour; Christian Cerezo-Navarrete; Carlos J. Gómez-García (Magnetochemistry)
Herein, we present the synthesis and structural characterisation of two layered MOFs with the asymmetric ligand 3-chloro,6-cyano-2,5-dihydroxy-1,4-benzoquinone dianion (C6O4(CN)Cl2− = chlorocyananilato). These compounds, formulated as (H3O)[Eu(C6O4(CN)Cl)2(H2O)]·34H2O (1) and (H3O)[Dy(C6O4(CN)Cl)2(H2O)]·44H2O (2), are isostructural and show a (4,4)-layered square structure with the crystallisation water molecules located between the layers. The lanthanoid ions are surrounded by four bis-bidentate chlorocyananilato ligands that connect each LnIII centre with other four, giving rise to square cavities formed by LnIII centres in the vertices and chlorocyananilato ligands as the sides. There is an additional coordinated water molecule that occupies the caped position of the capped square antiprismatic coordination geometry around the LnIII centres. The magnetic properties show the presence of a field-induced slow relaxation of the magnetisation in the DyIII derivative at low temperatures that follows Direct and Orbach relaxation mechanisms with an energy barrier of 36(3) K.